2002
DOI: 10.1086/344161
|View full text |Cite
|
Sign up to set email alerts
|

Metallicities of Old Open Clusters

Abstract: We present radial velocities and metallicities for a sample of 39 open clusters with ages greater than about 700 million years. For 24 clusters new moderate-resolution spectroscopic data obtained with multiobject spectrographs on the Kitt Peak National Observatory and the Cerro Tololo Inter-American Observatory 4 m telescopes are used to determine radial velocities and mean cluster metallicities. These new results are combined with data published previously by Friel & Janes to provide a sample of 459 giants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

94
590
16
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(707 citation statements)
references
References 88 publications
94
590
16
1
Order By: Relevance
“…However, not all the investigators have arrived at similar measures of the radial metallicity gradient which may be partly related to the different methods adopted (see for example, Magrini et al 2009;Heiter et al 2014). Our current understanding suggests a gradient of about −0.06 dex kpc −1 (Friel et al 2002;Pancino et al 2010) to −0.20 dex kpc −1 (Frinchaboy et al 2013) in the radial range 5 to 10 kpc with a nearly flat trend (−0.02 dex kpc −1 ) beyond 13 kpc (Carraro et al 2007;Sestito et al 2008;Pancino et al 2010;Yong et al 2012;Frinchaboy et al 2013;Cantat-Gaudin et al 2016).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, not all the investigators have arrived at similar measures of the radial metallicity gradient which may be partly related to the different methods adopted (see for example, Magrini et al 2009;Heiter et al 2014). Our current understanding suggests a gradient of about −0.06 dex kpc −1 (Friel et al 2002;Pancino et al 2010) to −0.20 dex kpc −1 (Frinchaboy et al 2013) in the radial range 5 to 10 kpc with a nearly flat trend (−0.02 dex kpc −1 ) beyond 13 kpc (Carraro et al 2007;Sestito et al 2008;Pancino et al 2010;Yong et al 2012;Frinchaboy et al 2013;Cantat-Gaudin et al 2016).…”
Section: Introductionmentioning
confidence: 85%
“…Abundance gradients in the Milky Way can be measured using a wide variety of tracers including the young population of H ii regions, OB stars, and Cepheid variables, and planetary nebulae of different ages, cool unevolved stars and red giants in the field (see for example, Magrini et al 2010;Cheng et al 2012;Hayden et al 2014) and in open clusters (OCs; Friel et al 2002Friel et al , 2010Magrini et al 2010;Pancino et al 2010;Yong et al 2012;Frinchaboy et al 2013). The cooler main sequence stars or red giants which are members of OCs provide not only abundance estimates for elements sampling all the major processes of stellar nucleosynthesis -but a collection of stars whose age, distance, kinematics and metallicity can be measured with greater certainty than for field stars.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 10 of their paper, these authors investigated the abundance gradient as a function of time by combining the results derived from OC data by Friel et al (2002), and by Chen et al (2003). The theoretical tracks of Chappini et al (2001) and Hou et al (2000), are also shown, respectively.…”
Section: The Disk Abundance Gradient Based On Open Clustersmentioning
confidence: 98%
“…References for the data in Columns 7-12 are listed in the last column. Peniche et al (1990), (2) Carraro & Vallenari (2000), (3) Friel et al (2002), (4) Tadross (2003), (5) Park & Lee (1999), (6) Canterna et al (1986), (7) Geisler et al (1991Geisler et al ( , 1992, (8) Friel & Janes (1993), (9) Jacobson et al (2008), (10) Claria et al (1989), (11) Piatti et al (1995), (12) Twarog et al (1997), (13) Carraro et al (2007), (14) Ann et al (2002), (15) Cameron (1985), (16) Claria et al (1999), (17) Table 7. If we are to do a large survey with between 300 and 500 OCs, such comparisons are necessary and useful to evaluate the consistency and quality of the results in the literature, and to provide the offsets between all these different studies, ours and those in the literature.…”
Section: Correlations Of the Interstellar Reddeningsmentioning
confidence: 99%